2018
DOI: 10.1002/jmv.25373
|View full text |Cite
|
Sign up to set email alerts
|

VDR rs7975232/ApaI genetic variation predicts sustained HBsAg loss in HBeAg‐positive chronic hepatitis B patients treated with pegylated interferon

Abstract: Aim To evaluate the predictive value of vitamin D and its metabolic pathway gene polymorphisms in response to pegylated interferon (Peg‐IFN) in hepatitis B early antigen (HBeAg)‐positive chronic hepatitis B (CHB) patients. Methods One hundred and nineteen HBeAg‐positive CHB patients who received Peg‐IFN monotherapy for 48 weeks and then were followed‐up for another 48 weeks were prospectively enrolled; baseline 25‐hydroxy vitamin D (25‐(OH)D) and hepatitis B virus serologic marker levels were detected, nine cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In line with this, VDR ApaI was also associated with the clinical outcome of and liver disease progression in HBV patients [130]. From a therapeutic perspective, VDR rs7975232/ApaI was identified as a pretreatment predictor of sustained HBsAg seroclearance in HBeAg-positive HBV patients when treated with PEG-IFNα [131]. In support of this, VDR ApaI SNP was associated with viral loads and the presence of HBsAg in response to PEG-IFNα treatment [132].…”
Section: Effect Of Vdrg Polymorphisms On Hbv Infection Pathogenesismentioning
confidence: 66%
“…In line with this, VDR ApaI was also associated with the clinical outcome of and liver disease progression in HBV patients [130]. From a therapeutic perspective, VDR rs7975232/ApaI was identified as a pretreatment predictor of sustained HBsAg seroclearance in HBeAg-positive HBV patients when treated with PEG-IFNα [131]. In support of this, VDR ApaI SNP was associated with viral loads and the presence of HBsAg in response to PEG-IFNα treatment [132].…”
Section: Effect Of Vdrg Polymorphisms On Hbv Infection Pathogenesismentioning
confidence: 66%
“…Other studies have shown, that polymorphism rs2228570 (FokI) genotype ff makes people more susceptible to hepatitis B and also hepatocarcinoma [ 169 , 170 ]. Other studies have shown that rs7975232 (ApaI) polymorphism increases the liver damage risk caused by HBV [ 171 ]; this polymorphism is also a prognostic factor in the effectiveness of treatment of hepatitis patients with Peg-IFN monotherapy [ 172 , 173 ]. In a study about the rs222020 variant, which is linked to the vitamin D-binding protein gene, Hbe-negative individuals who received Peg-IFN treatment were found to have normal levels of ALT liver enzymes, as well as lower Hbs antigen levels [ 174 ].…”
Section: Role Of Vitamin D In Immune Systemmentioning
confidence: 99%